HAKIKAT BELAJAR DAN BERMAIN MENYENANGKAN BAGI PESERTA DIDIK - Zulvia Trinova (AT-TA'LIM, 2012)
Learning is a process of knowledge development, skill, and attitude through intensive interaction with learning resources. Learning by playing to the the children provide a chance to manipulate, reiterate, explore, practice, take many concepts. Learning by fun is a process of learning in fun and meaningful situation that can attract students’ interest to be involve actively, so that learning purpose can be achieve maximally.